2019
DOI: 10.25186/cs.v14i4.1615
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of the Herbicide Chlorimuron Ethyl on Young Coffee Plants

Abstract: The great interference of weeds in coffee plants, due to competition for water, light and nutrients, makes their control essential. Among these control methods, the chemical stands out, due to its high efficiency and low cost. However, as a function of application failures, phytotoxicity is frequent in coffee plants due to herbicide drift. Aiming to search for active ingredients selective to coffee, the objective of this study was to evaluate the selectivity of the active ingredient Chlorimuron ethyl in coffee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…As well as the symptoms of phytotoxicity, the time factor is also crucial for observing changes in anatomical leaf characteristics in coffee plants submitted to herbicide application. In this work, changes in anatomical leaf characteristics were identified at 65 DAA, despite that, Voltolini et al (2019) and Castanheira et al (2019a) did not find influence of these characteristics at 120 DAA of the herbicides fluazifop-p-butyl and chlorimuron-ethyl respectively.…”
Section: Anatomical Featurescontrasting
confidence: 54%
See 3 more Smart Citations
“…As well as the symptoms of phytotoxicity, the time factor is also crucial for observing changes in anatomical leaf characteristics in coffee plants submitted to herbicide application. In this work, changes in anatomical leaf characteristics were identified at 65 DAA, despite that, Voltolini et al (2019) and Castanheira et al (2019a) did not find influence of these characteristics at 120 DAA of the herbicides fluazifop-p-butyl and chlorimuron-ethyl respectively.…”
Section: Anatomical Featurescontrasting
confidence: 54%
“…One of the main mechanisms that confer the natural tolerance of some plant species to ALS-inhibiting herbicides is metabolism at the non-target site (Yu;Powles, 2014), which explains the deformity of the leaves of coffee trees when treated with this group of herbicides, showing that phytotoxic effects occur at the application site. Castanheira et al (2019a) reported deformations and fissures in the leaves of coffee seedlings 120 days after the application of chlorimuron-ethyl. In the same way, Ronchi and Silva (2003) observed mild symptoms that appeared late in newly planted coffee trees after simulated drift of this herbicide.…”
Section: Phytotoxicity Assessmentmentioning
confidence: 99%
See 2 more Smart Citations